2020
DOI: 10.1007/s00431-020-03805-2
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of diaphragmatic thickness and excursion as a predictor for successful extubation in mechanically ventilated preterm infants

Abstract: Sonographic assessment of diaphragmatic thickness and excursion has been found to be an accurate tool in predicting successful extubation of adult patients from invasive mechanical ventilation. We aimed to evaluate the accuracy of sonographic assessment of diaphragmatic thickness and excursion in predicting successful extubation of preterm infants from invasive conventional mechanical ventilation. Preterm infants less than 32 weeks gestation who required invasive conventional mechanical ventilation were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 32 publications
4
33
1
Order By: Relevance
“…Regarding GA, it is well known that age is negatively correlated with excursion in deep breathing, and that females have less diaphragmatic excursion than male (26) . While in our study no difference in sex was detected yet, a significant difference between full-term and pre-term neonates was detected which matches the study results of Bahgat et al (25) . In the contrary, Johnson et al (27) have revealed that diaphragmatic atrophy in intubated critically ill children have occurred rapidly and irrespectively of age.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding GA, it is well known that age is negatively correlated with excursion in deep breathing, and that females have less diaphragmatic excursion than male (26) . While in our study no difference in sex was detected yet, a significant difference between full-term and pre-term neonates was detected which matches the study results of Bahgat et al (25) . In the contrary, Johnson et al (27) have revealed that diaphragmatic atrophy in intubated critically ill children have occurred rapidly and irrespectively of age.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mortality rate in the successful weaning group was 4.3% in full term and 8.7% in preterm, while in weaning failure group it was 8% and 24% in full-term and preterm respectively, which matches with the results of other studies (25,27) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This nding is suggested that evaluating excursion can be a sensitive method for determination of diaphragm function in preterm babies. Indeed, a previous study investigating successful extubation in preterm babies by diaphragm US reported higher thicknesses and excursions in the successfully extubated group 23 . The researchers also stated that the excursion was the most useful indicator for successful extubation.…”
Section: Discussionmentioning
confidence: 90%